Dissolution of Parliament in Constitutional Systems: A Comparative Analytical Study - Saeed, Dana AbdulKareem; Maarouf, Sefin Kamal (Journal of Legal and Political Studies, 2023)
In contemporary constitutional systems, the dissolution of Parliament is one of the main guarantees in achieving a balance between the legislative and executive powers. However, the constitutions differed in their organization, whether in terms of the reasons that require resorting to it, the authorities in charge of it, or the guarantees that guarantee its proper conduct and prevent the executive authority from arbitrarily using it. This research sheds light on the various topics related to the dissolution of Parliament with regard to its concept, types, reasons for resorting to it, and its guarantees, and through this, an explanation of its importance and role in achieving balance between the legislative and executive powers. The research also addresses, in part, the constitutional regulation for dissolving the House of Representatives in both the Constitution of the Republic of Iraq for the year 2005 and the Constitution of the Arab Republic of Egypt for the year 2014. The research concludes with a number of conclusions stemming from it, as well as a set of recommendations addressed to the Iraqi legislator for the purpose of reconsidering the constitutional organization for dissolving the House of Representatives in the Constitution of the Republic of Iraq for the year 2005.
Keywords: contemporary constitutional systems; Parliament; proper conduct; executive powers; Constitution of the Republic of Iraq